2013
DOI: 10.1007/s11557-013-0900-z
|View full text |Cite
|
Sign up to set email alerts
|

Multigene phylogeny, taxonomy and reclassification of Hyaloperonospora on Cardamine

Abstract: Based on sequence data from cox1, cox2, ITS and LSU rDNA, it is shown that at least six species of Hyaloperonospora occur on the genus Cardamine, most of which were commonly classified under Peronospora dentariae. Based on sequences from their type hosts, Peronospora dentariae, Peronospora cardamines-laciniatae, Peronospora dentariae-macrophyllae, Peronospora malyi and Peronospora nasturtii-aquatici are combined into Hyaloperonospora, and their circumscription is clarified. Hyaloperonospora cardamines-enneaphy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
12
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 37 publications
(53 reference statements)
4
12
0
Order By: Relevance
“…Note: This cosmopolitan species is parasitic to four different species of Cardamine , including C. impatiens . The morphology fits well with the description of H. dentariae collected from C. heptaphylla [ 3 12 ], except for minor differences in the conidial size. In the cox 2 tree, as suggested by Voglmayr et al [ 12 ], there were a few subclades within “ H. dentariae complex”, among which the Korean samples formed a well-supported group ( Fig.…”
Section: Resultssupporting
confidence: 76%
See 3 more Smart Citations
“…Note: This cosmopolitan species is parasitic to four different species of Cardamine , including C. impatiens . The morphology fits well with the description of H. dentariae collected from C. heptaphylla [ 3 12 ], except for minor differences in the conidial size. In the cox 2 tree, as suggested by Voglmayr et al [ 12 ], there were a few subclades within “ H. dentariae complex”, among which the Korean samples formed a well-supported group ( Fig.…”
Section: Resultssupporting
confidence: 76%
“…The Korean accessions collected from Cardamine impatiens fell within the H. dentariae clade, with weak supporting values in ITS dataset and the maximum value in cox 2 mtDNA. In the cox 2 dataset, they further formed their own well-supported subclade with the maximum supporting value in both analyses, as shown by Voglmayr et al [ 12 ], who observed the presence of host-specific substructures within the H. dentariae clade. Interestingly, there was a phylogenetic divergence between European and Korean accessions originating from the same plant, C. impatiens .…”
Section: Resultssupporting
confidence: 61%
See 2 more Smart Citations
“…[37], [47][63]), demonstrating that high biodiversity is commonly the result of high host specificity. Peronospora from Papaver are distributed amongst three clades (Figure 1), of which P. cristata from clade 1 is phylogenetically isolated from the other Peronospora species from Papaver , but clades 2 and 3 appear to be closely related (Figure 1).…”
Section: Discussionmentioning
confidence: 99%